Measurement of bearing load in unicompartmental knee arthroplasty using an instrumented knee bearing - Mentink, M; Dr Michael JA Mentink (2014)
The aim of this thesis was to investigate how to construct a system to measure load in a mobile unicompartmental knee replacement (UKR) bearing. In vivo loads have been measured in a total knee replacement (TKR), but with TKR the kinematics are different from those of the normal knee, whereas they are close to normal in a mobile UKR, so the loads measured by an instrumented UKR would be more representative of the normal knee. On the principle of measuring compression of an object under load, the load may be estimated. Compression measurement using a capacitive sensor was the optimal solution to measure load, based on life expectancy of the sensor and bearing integrity. A capacitive sensor within a polyethylene (UHMWPE) bearing has not been used before. The visco-elastic and temperature dependent properties of UHMWPE were determined with experiments. UHMWPE had an approximately linear response after ten minutes of applying a constant load. A temperature sensor should be used in vivo to compensate for temperature effects acting on the elastic modulus of UHMWPE. Finite element modelling demonstrated that positioning the sensor under the centre of the bearing concavity resulted in the largest capacitive change. The influence of various dimensional parameters on sensor output was simulated, and the conclusion was that the sensor only needs to be calibrated once. An electronic module inserted into a bearing had less than 5 % influence on bearing compression. Capacitive sensors were made from polyimide, using standard production methods, and embedded within a UKR bearing using the standard compression moulding process. The embedded sensor had a second order low pass frequency response, with a corner frequency of 9 Hz, twice the frequency required for typical functional loading such as gait. Physiological load signals, gait and step up/down, were applied to the bearing. The capacitance to load response was approximately linear. Load was estimated using a linear method and a dynamic method. The linear method performed best, with an accuracy of force estimation better than 90 %. In vitro tests were performed using a commercially available transceiver, two stan- dard antennas and a custom antenna, designed to be incorporated in the bearing. Wireless communication between an implanted custom antenna and an external an- tenna was shown to be feasible. Experiments were also performed that demonstrate that inductive powering of the bearing was feasible. In addition to load measurement, a proposal for dynamic measurement of the orien- tation angles of both the tibia and the femur was made. Power and volume calculations showed that it is possible to place an electronic module within the bearing. This thesis has not only demonstrated that it is feasible to make an instrumented bearing for UKR but has also provided a basic design for manufacturing.